Effect of intercropping with legumes at different rates on the yield and soil physicochemical properties of Cyperus esculentus L. in arid land - Shen, Xin; Liu, Yalan; Li, Xiangyi; Li, Lei (Frontiers in Plant Science, 2024)
Intercropping has the potential to enhance yields and nutrient availability in resource-limited agricultural systems. However, the effects on crop yield nutrients and soil properties can vary considerably depending on the specific plant combinations and intercropping ratios used. In this study, the advantages and impacts of intercropping C. esculentus with legumes were investigated by measuring their biomass, nutrient content, and soil properties. The experiment included five intercropping treatments: monoculture of C. esculentus (MC), intercropping of C. esculentus with Medicago sativa L. (alfalfa) at row spacing ratios of 4:4 (4:4CM) and 8:4 (8:4CM), and intercropping of C. esculentus with Glycine max (L.) Merr. (soybean), also at row spacing ratios of 4:4 (4:4CG) and 8:4 (8:4CG). Our results demonstrated that all four intercropping treatments (4:4CM, 4:4CG, 8:4CM, and 8:4CG) significantly increased the biomass of C. esculentus by approximately 41.05%, 41.73%, 16.08%, and 18.43% respectively compared with monoculture cultivation alone, among which the 4:4CG treatment was optimum. However, no significant differences were observed in alfalfa or soybean biomass across different intercropping ratios. A notable increase was found in the total nitrogen (TN) and total phosphorus (TP) contents in the leaves, roots, and tubers of C. esculentus under intercropping, along with increased soil organic carbon (SOC), alkaline-hydrolyzed nitrogen (AN), available phosphorus (AP), microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and soil water content (SWC) and significantly reduced soil pH. Among the intercropping treatments, the 4:4CG treatment also exhibited the most favorable soil properties. In particular, compared with MC, the 4:4CG treatment resulted in significant increases of 163.8%, 394.6%, and 716.8% in SOC, AN, and AP contents, respectively. The same treatment also led to significant increases of 48.34%, 46.40%, and 208.65% in MBC, MBN, and SWC respectively. Overall, the findings suggest that the use of 4:4CG intercropping is an effective approach for sustainable farming management in Xinjiang.